Co-expression of HBZ, TAX and FOXp3 and HTLV-1-associated myelopathy/ tropical spastic paraparesis development in HTLV-1-infected individuals: A systematic review - Lima, Ana; da Silva, Greice; Barreto, Fernanda; Rego, Filipe; Gois, Luana; Santos, Luciane (Asian Pacific journal of tropical medicine, 2021)
Human T-cell lymphotropic virus type 1 (HTLV-1) is associated with the development of HTLV-1-associated myelopathy/tropical spastic paraparesis (HAM/TSP). It has been reported that the HTLV-1 proteins (specifically TAX and HBZ) can modulate FOXp3, resulting in an immune imbalance that can favor the progression of HAM/TSP. This review aims to summarize the literature in order to clarify the relationship between the expression of HTLV-1 mRNAs and/or viral proteins (TAX and HBZ) with the expression of mRNA and/or protein FOXp3 and their correlation with HAM/ TSP development. This systematic review was conducted according to the recommendations of the Preferred Reporting Items for Systematic Reviews and Meta-Analysis. The search strategy was performed on the Medical Literature Analysis and Retrieval System Online and Latin American and Caribbean Literature in Health Sciences Platform using subject descriptors. After screening, six articles were included in this review. The studies suggested that TAX and HBZ have a directly proportional correlation with FOXp3 in individuals with HAM/TSP, which also presented an increased expression of FOXp3 compared to asymptomatic controls and/or healthy donors. This systematic review indicates that TAX and HBZ can interact with FOXp3 and that interaction may influence HAM/ TSP development.